The effects of child care subsidies on paid child care participation and labor market outcomes: Evidence from the child and dependent care credit - Gabrielle Pepin (W.E. Upjohn Institute for Employment Research, 2020)
The Child and Dependent Care Credit (CDCC), a tax credit based on taxpayers' income and child care expenses, reduces families' child care costs. The nonrefundable federal CDCC is available to working families with children younger than 13 years old in all states, and nearly half of states supplement the federal credit with their own child care credits. The Economic Growth and Tax Relief Reconciliation Act expanded the federal CDCC in 2003, which led to differential increases in CDCC generosity across states and family sizes. I document CDCC eligibility and expenditures over time and across income and demographic groups. Using data from the March Current Population Survey, I find that a 10 percent increase in CDCC benefits increases annual paid child care participation by 4-5 percent among households with children younger than 13 years old. I also find that CDCC benefits increase labor supply among married mothers. Increases in labor supply among married mothers with very young children suggest that CDCC benefits may generate long-run earnings gains.
Keywords: J13; H24; J22; H71; 330; Child care subsidies; female labor supply; instrumental variables; participation